Automatic estimation of kinetic and isotherm parameters from ZLC experiments. (14th April 2015) - Friedrich, Daniel; Mangano, Enzo; Brandani, Stefano
Abstract: In order to automate and improve the analysis of the experimental Zero Length Column (ZLC) data a general adsorption simulator is applied to the simulation of the ZLC system. The output of this ZLC simulation is linked to a hybrid optimisation strategy: combining a global Genetic Algorithm (GA) with a local Nelder–Mead algorithm ensures an efficient and accurate optimisation procedure. By minimising the deviation between the experimental data and the simulation the kinetic and equilibrium parameters of the adsorbent can be estimated. In the first step the parameters of the blank experiment are fitted; thus taking the dynamics of the detector and the system piping into account. In the second step several experiments at different flow rates and temperatures are fitted simultaneously. This increases the accuracy and reliability of the results. The automated parameter estimation was applied to ZLC runs with carbon dioxide on zeolite 13X pellets. The results agree with the traditional analysis methods and with independent measurements. In addition it is demonstrated that it is possible to approximate the correct adsorption isotherm from ZLC runs under kinetic control. The automatic analysis tool allows the inclusion of nonlinear effects in the fitting and lowers the access barrier to the application of the ZLC method. Highlights: Automated estimation of kinetic and equilibrium parameters from ZLC curves. Simulation of the ZLC desorption curves with a general adsorption process simulator. Explicit handling of the detector kinetics and inclusion of nonlinear effects. Improved accuracy, reliability and ease of use compared to an analytical method. Estimate the correct adsorption isotherm from ZLC runs under kinetic control.